Ambiguity, Transparency, and Institutional Strength - Erbas, S. (Washington, D.C. : International Monetary Fund, 2004)
Institutional transparency makes future contingencies more easily predictable for investors. Greater transparency can be achieved through vertical and horizontal integration of policy rules, which may result in lower Knightian uncertainty (ambiguity). In a model based on cumulative prospect theory, for a given probability and payoff structure, expected return on investment is higher in more transparent countries; therefore, those countries attract more investment and grow faster than less transparent countries. Lower transparency may result in inherently higher volatility.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Analysis Of Collective Decision-Making; Expected Return; Horizontal Integration; Vertical Integration; WP